Upper Paleolithic cultural diversity in the Iranian Zagros Mountains and the expansion of modern humans into Eurasia. Issue 132 (July 2019) - Ghasidian, Elham; Heydari-Guran, Saman; Mirazón Lahr, Marta
Abstract: This paper aims to understand the cultural diversity among the first modern human populations in the Iranian Zagros and the implications of this diversity for evolutionary and ecological models of human dispersal through Eurasia. We use quantitative data and technotypological attributes combined with physiogeographic information to assess if the Zagros Upper Paleolithic (UP) developed locally from the Middle Paleolithic (MP), as well as to contextualize the variation in lithics from four UP sites of Warwasi, Yafteh, Pasangar, and Ghār-e Boof. Our results demonstrate (1) that the Zagros UP industries are intrusive to the region, and (2) that there is significant cultural diversity in the early UP across different Zagros habitat areas, and that this diversity clusters in at least three groups. We interpret this variation as parallel developments after the initial occupation of the region shaped by the relative geotopographical isolation of different areas of the Zagros, which would have favored different ecological adaptations. The greater similarity of lithic traditions and modes of production observed in the later phases of the UP across all sites indicates a marked increase in inter-group contact throughout the West-Central Zagros mountain chain. Based on the chronological and geographical patterns of Zagros UP variability, we propose a model of an initial colonization phase leading to the emergence of distinct local traditions, followed by a long phase of limited contact among these first UP groups. This has important implications for the origins of biological and cultural diversity in the early phases of modern human colonization of Eurasia. We suggest that the mountainous arc that extends from Anatolia to the Southern Zagros preserves the archaeological record of different population trajectories. Among them, by 40 ka, some would have been transient, whereas others would have left no living descendants. However, some would have led to longer term local traditions, including groups who share ancestry with modern Europeans and modern East/Southeast Asians.